Ultrasound-assisted extraction of triterpenoids from Chaenomeles speciosa leaves: Process optimization, adsorptive enrichment, chemical profiling, and protection against ulcerative colitis - Mengyang Hou; Jingchun Shi; Chengyuan Lin; Lin Zhu; Zhaoxiang Bian (Ultrasonics Sonochemistry)
For the valorization of Chaenomeles speciosa leaves, this study focused on extraction, enrichment, chemical profiling, and investigation of the biological activity of its abundant triterpenoid components. Initially, the total triterpenoids in C. speciosa leaves were extracted by ultrasonic-assisted extraction (UAE) method, with the extraction process optimized through response surface methodology (RSM). Under the optimal conditions of extraction solvent 93 % EtOH, ultrasound power 390 W, extraction time 30 min, extraction temperature 70 °C, liquid-to-solid ratio 25 mL/g, and 2 extraction cycles, the maximum total triterpenoids yield (TTY) reached 36.77 ± 0.40 mg/g. The total triterpenoids in the crude extract were subsequently enriched by X-5 resin column chromatography, resulting in a fourfold increase in purity, reaching 73.27 ± 0.84 %. Thirteen compounds in the triterpenoid-rich fraction (TRF) were identified through UPLC–QTOF-MS/MS, and five major triterpenoids (oleanolic acid, ursolic acid, betulinic acid, maslinic acid, and pomolic acid) were simultaneously quantified by HPLC–QQQ-MS. Furthermore, TRF demonstrated a notable amelioration against dextran sodium sulfate (DSS)-induced ulcerative colitis in mice, indicating its promise as a potent intervention for this condition. In summary, this study will contribute to enhancing the utilization efficiency of Chaenomeles speciosa leaves.